Feasibility and Acceptability of a Remotely Delivered Weighted Blanket Intervention for People Living With Dementia and Their Family Caregivers. (November 2022) - Harris, Melissa L.; Titler, Marita G.
The COVID-19 pandemic amplified the need for interventions to support community-dwelling families living with dementia. This study examined the feasibility and acceptability of a remotely delivered weighted blanket intervention for people living with dementia, and the feasibility of collecting outcome measures specific to people with dementia and caregivers. A prospective, within subjects, pre-post design was used; 21 people with dementia and their caregivers participated. Measures of feasibility (days blanket was used for the recommended duration, injuries/adverse events, enrollment, and withdrawal rate, time to recruit sample) and acceptability (tolerability, satisfaction, and benefit perceived by participants with dementia and caregivers) were examined. Feasibility of collecting measures was examined through missing data. Results indicated high feasibility and acceptability. Collecting caregiver completed outcome measures was feasible, but measures completed by self-report by people with dementia was not. Weighted blankets are a promising tool for this population that warrant further examination to determine efficacy.